Penerapan Model PJBL Untuk Meningkatkan Keterampilan Proses dan Hasil Belajar Matematika Materi Bangun Ruang Sisi Datar Kelas VIII C SMP Negeri 4 Sumbang Semester 2 Tahun Pelajaran 2016/2017 - Theresia Warsini (AlphaMath : Journal of Mathematics Education, 2019)
The results of learning mathematics at SMPN 4 Sumbang are still low. This is caused by the factors of students who are less active, lazy, and easily bored, while teachers who have difficulty learning students, but students who do not like to learn mathematics. Therefore it is necessary to improve learning outcomes so that researchers apply the PjBL (Project Based Learning) model to enhance the process skills and mathematics learning outcomes of flat side space material. The research objective to be achieved is to find out whether the PjBL learning model can improve the learning process and the learning outcomes of mathematics in flat side space. This research is a Classroom Action Research. Learning tools, namely syllabus, lesson plans, teaching materials, and worksheets. While the research instrument is the description test and observation sheet. The subjects of the research were the students of class VIII C of SMP N 4 Sumbang with 22 students. The study was conducted in February through June 2017. The subject and time of the study were chosen because the researcher taught in the class, and the implementation time was adjusted to the lesson schedule. The research procedure begins with a discussion of the problem, planning of the action, implementing the action and observation, as well as analysis and reflection. The results of research that can answer the problem formulation achieve research objectives and prove research hypotheses about the application of the PjBL learning model can improve the process skills and learning outcomes of mathematics material in the scope of class VIII C students of SMP N 4 Sumbang 2016/2017 school year. This situation is proven by the results of the first cycle of highly competent students as much as 18%, cycle II as much as 45% and cycles III as much as 55%. Student learning outcomes on average 63.64 in the first cycle, 68.73 in the second cycle, and increased again to 75.27 at the end of the third cycle. From these results, it was agreed by the teacher to develop the PjBL learning model in the material that would be presented later to improve student learning outcomes. In contrast, students appreciate enhancing the learning process when learning and better prepare themselves before the learning process begins.